DEL TO (¿TRASCENDENTAL?) AL NOSOTROS (¿INTRASCENDENTAL?) LA LECTURA DE KANT EN EL NEOKANTISMO CONTEMPORÁNEO - Muguerza, Javier (Daimon Revista Internacional de Filosofia, 2004)
Prompted, maybe, by Apel and Habermas’reading of Kant («contemporary neokantism»), the author analyzes a passage thatconstitutes a contribution of Kant; namely, the passagefrom the «I» to the «us». The analysis of thisstep, although it evokes what goes from Kant toHerder and Hegel, focuses on situations such as thelinguistic transformation of transcendental philosophyand Apel; the ideal community of communication,and real or sociohistoric communities; andthe habermasian version of discourse consciousness.The interest of the author is to emphasize, despitethe goodness of the linguistic turn, that whatproves decisive is the doble step already found inKant himself: i) from the I of the ‘pure aperception’to the «us» of the ‘ends kingdom’, and ii) from‘transcendental’ to ‘moral conscience’, basis of theexistential irreducibility of the moral subject.The author inquires with regard to thepassage from the «I» to the «us» what constitutes acontribution by Kant in this respect, perhapsrelying on Apel and Habermas’ reading of Kant(«contemporary neokantism»). The analysis of thisstep, although evoking what goes from Kant toHerder and Hegel, focuses on situations such thelinguistic transformation of transcendental philosophyand Apel; the ideal community of communication,and real or sociohistoric communities; andthe habermasian version of discourse consciousness.The interest of the author is to emphasize,despite the goodness of the linguistic turn, thatwhat proves decisive is the doble step alreadyfound in Kant himself: i) from the I of the ‘pureaperception’ to the «us» of the ‘ends kingdom’, ii)from ‘transcendental’ to ‘moral conscience’, basisof the existential irreducibility of the moral subject.